The dynamics of relief spending and the private urban labor market during the New Deal - Neumann, Todd; Fishback, Price 1955-; Kantor, Shawn Everett (Working paper series / National Bureau of Economic Research, 2007)
During the New Deal the Roosevelt Administration dramatically expanded relief spending to combat extraordinarily high rates of unemployment. We examine the dynamic relationships between relief spending and local private labor markets using a new panel data set of monthly relief, private employment and private earnings for major U.S. cities in the 1930s. Impulse response functions derived from a panel VAR model that controls for time and city fixed effects show that a work relief shock in period t-1 led to a decline in private employment and a rise in private monthly earnings. The finding offers evidence consistent with contemporary employers' complaints that work relief made it more difficult to hire, even though work relief officials followed their stated policies to avoid affecting private labor markets directly. Meanwhile, negative shocks to private employment led to increases in work relief, consistent with Roosevelt's stated goal of using relief to promote relief and recovery.